Fruit and vegetable freshness detection using deep learning - Haque, Md. Mahidul; Ahmed, Rehanul; Saha, Somak; Saha, Chamak; Dutta, Mayurakshmi (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.